Orchid Plant Business Development Plan Griya Kembang Punakawan - Riza Pahlevi; Yenny Maya Dora (Eduvest - Journal of Universal Studies, 2025)
The ornamental plant industry, especially orchids, has experienced significant growth along with the increasing public interest in natural decorations. This study aims to ana-lyze the development strategy of orchid cultivation and rental businesses as a sustaina-ble business model. The research method used is a qualitative approach with a case study on Griya Kembang Punakawan, a business that integrates orchid cultivation, rent-al, and care clinics in Greater Bandung. The results of the study indicate that the imple-mentation of an integrated business model provides a competitive advantage by in-creasing the added value of products and services. Orchid rental services for events such as weddings and exhibitions are an economical alternative compared to purchasing ornamental plants directly. In addition, orchid clinic services contribute to maintaining plant quality by offering care consultations. From a financial aspect, business projections show a positive return on investment, with an estimated ROI of 70.64% per year and an NPV reaching IDR 435,151,581. In conclusion, the orchid cultivation and rental business development strategy has promising prospects in supporting business sustainability, especially with the optimization of digital marketing and efficient supply chain management.